Magnetic chemiluminescent immunoassay for human C-reactive protein on the centrifugal microfluidics platform1. Issue 76 (19th August 2015) - Czilwik, G.; Vashist, S. K.; Klein, V.; Buderer, A.; Roth, G.; von Stetten, F.; Zengerle, R.; Mark, D.
<x xml:space="preserve">Abstract</x> Schematic of the LabDisk-based hCRP MCIA. The antibody-coated dynabeads are sequentially transported through the immunoassay buffers by magnetic actuation. Finally the chemiluminescence signal is acquired from a detection cavity.